The Practices of Green Supply Chain Management towards Corporate Performances in Construction Industry - Jing, Khoo Terh; Ismail, Radzi Bin; Yee, Ha Chin; Shafiei, Mohd Wira Mohd; Wai, Tee Kah (International Journal of Supply Chain Management, 2019)
Green Supply Chain Management (GSCM) practices has different impact on the corporate performances while practitioners are not willing to implement practices that is irrelevant to their organization. Hence, to ensure the most appropriate investment on GSCM is implemented, this study is conducted to identify the relationship between GSCM practices and corporate performances in Malaysia construction industry. To conduct a literature review to figure the relationship between GSCM practices and corporate performances. Systematic literature review method is adopted in data collection stage. The findings of the study show that the green practices are correlated to the corporate performances and a comprehensive conceptual framework is formed from this study to describe the relationships between GSCM practices and corporate performances in Malaysia construction industry. Research on GSCM in Malaysia is still less in construction industry. However, the findings provide crucial insights for potential practitioners due to it consistency with prior studies which are related to GSCM in other industries and countries. Implementation of GSCM improves corporate performances in various dimensions. The construction industry should understand the functions and relationship of each element in GSCM to achieve best performance outcome in the form they desired. A comprehensive conceptual framework which shows the relationships of GSCM and its impact construction industry which allow the potential practitioners to understand the potential improvement in corporate performances is constructed through the systematic literature review.